Detection of thrombosis in microvessels with indocyanine green videoangiography. Issue 8 (October 2018) - Mücke, T.; Wolff, C.; Fichter, A.M.; von Düring, M.; Kanatas, A.; Ritschl, L.M.
Abstract: Atherosclerosis is a systemic condition that is responsible for many diseases, and becomes a problem in cases where plaques form at several sites. The formation of a thrombotic embolus may jeopardise vascular operations, including microvascular anastomoses in replantation procedures or free tissue transfers. A mobile imaging tool for the detection of thrombosis preoperatively or intraoperatively would be valuable. An intimal injury, simulating removal of atherosclerotic plaques, was made microsurgically in 60 rat aortas, and results were analysed macroscopically, histologically, and with intraoperative indocyanine green (ICG) videoangiography immediately postoperatively. The Spearman and Pearson correlation tests were used to compare the three techniques. The sensitivity and specificity of ICG videoangiography was calculated in relation to both macroscopic and histological results. Detection of thrombosis was possible in 25 cases, and in 18 cases no thrombosis was correctly diagnosed by all methods used. In 31 of 60 specimens formation of thrombus was detected histologically, and in 29 of 60 examinations it was detected clinically, which yielded a correlation of 93.5% between the two examinations. Macroscopic analysis correlated better with ICG videoangiography (sensitivity 86.2% and specificity 64.5%) than histological observations (sensitivity 80.6% and specificity 62.1%). There was a significant correlation among all comparisons (each p ≤ 0.001) with correlation indexes of 0.94, 0.52, and 0.44 for macroscopic/histological, clinical/ICG videoangiographic, and ICG videoangiographic/histological results, respectively. Our results show that ICG videoangiography is an important method for the detection of formation of acute thrombi and may be an important tool in vascular procedures.